Two new spongian diterpene analogues isolated from the marine sponge Acanthodendrilla sp. Issue 8 (17th April 2020) - Costa, Margarida; Fernández, Rogelio; Pérez, Marta; Thorsteinsdottir, Margrét
Abstract: Two new marine natural compounds, 3β-acetoxy-15-hydroxyspongia-12-en (1 ) and 3-methylspongia-3, 12-dien-16-one (2 ), were isolated from the marine sponge Acanthodendrilla sp., collected in Pulau-Pulau. Compounds 1 and 2 represent new chemical entities of the known spongian diterpene family. Compound 1 is a new 3-acetoxyspongia and compound 2 presents an unreported rearranged 3-methylspongia-3-en. Their structures, including relative configurations, were fully elucidated based on 1D and 2D NMR analyses, as well as HRESTOFMS experiments. No significant bioactivities were found for these compounds. This work reports two new chemical structures, compounds 1 and 2, together with the first isolation of spongian diterpenes from Acanthodendrilla genus. Graphical Abstract: